Morphologically dependent alternating‐current and direct‐current breakdown strength in silica–polypropylene nanocomposites. Issue 1 (4th September 2016) - Krentz, Timothy; Khani, Mohammad M.; Bell, Michael; Benicewicz, Brian C.; Nelson, J. Keith; Zhao, Su; Hillborg, Henrik; Schadler, Linda S.
ABSTRACT: In this article, we report the synthesis of a new bimodal surface ligand morphology on silica nanoparticles. Combining grafting‐to and grafting‐from approaches, in this study, we demonstrated the efficacy of anthracene surface modification for improving the dielectric breakdown strength (DBS) under alternating‐current and direct‐current conditions and that of a matrix‐compatible polymer brush for controlling the nanofiller (NF) dispersion. Ligand‐modified spherical colloidal SiO2 nanoparticles (∼14 nm in diameter) were mixed into polypropylene, and the resulting dispersion was improved over the unmodified particles, as shown with transmission electron microscopy. The results suggest that the electronic structure of the anthracene‐modified particle surface was critical to the improvement in DBS. In addition, the DBS of the composite was shown to depend on the dispersion state of the filler and the mode of stress; this indicated that the individually dispersed nanoparticles were not necessarily the optimal morphology for all stress conditions. Additionally, the precise nature of the matrix‐compatible brush was less important than the NF dispersion it produced. The bimodal grafted architectural design has provided a promising solution for the control of the dispersion and surface properties, especially for high‐molecular‐weight polymer matrices. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44347. Abstract :